P180 Sputum eosinophil positivity to tailor steroid management of severe asthmatics. (16th November 2010) - Tavernier, G; Pris-Picard, C; Gore, R; Niven, R
Abstract : The use of sputum eosinophil count in asthma clinics is rapidly expanding as it has been reported as being a useful indicator of the worsening of asthma symptoms and that its normalisation reduces asthma exacerbations and admissions. Without additional steroids, levels of sputum eosinophils have been shown to be highly variable in severe asthmatic patients. Furthermore, precise patient phenotyping is increasingly becoming important as our understanding of the physiopathology of severe asthma widens. We introduced sputum differential cell counting in our severe asthma clinic, with a view to first reducing sputum eosinophils below 3% by augmenting anti-inflammatory therapy, and attempting steroid withdrawal once patients became sputum eosinophil negative (E−). To date, 264 patients have been investigated for sputum eosinophils, using induction with nebulised sodium chloride if necessary and suitable. This paper presents our yearly update of the anti-inflammatory (steroid) therapy of the first successive patients with at least two successful sputum counts (current n=71), specifically investigating patients' management in the light of their positive sputum eosinophil levels at baseline assessment. Twenty patients were sputum eosinophil positive (E+) on their initial visit and 25 had reduced eosinophil levels (p=0.001) on a subsequent visit, including 14 becoming E−. Nineteen were offered a trial of steroid augmentation: 11 patients with a trial of IM triamcinolone (all patients had subsequent reduced eosinophils levels, 9 becoming E−, p=0.003); 5 patients with increased oral prednisolone treatment (four patients with reduced eosinophils levels, one becoming E−); 3 with increased inhaled steroid therapy (all with reduced eosinophil levels, 1 becoming E−). 66% of patients with uncontrolled sputum eosinophilia were treated with an increase in anti-inflammatory maintenance therapy. Sputum eosinophil levels decreased for 95% of these as already reported, but only 11/19 achieved full control of sputum eosinophilia with 2/11 failing to normalise eosinophils despite IM triamcinolone (representing a population of confirmed steroid resistance. Sputum eosinophil negativity used as a surrogate marker for asthma control has been shown to be an essential tool in identification and management of patients with asthma at risk of deterioration and admission.